2004
DOI: 10.1212/01.wnl.0000145842.25520.a2
|View full text |Cite
|
Sign up to set email alerts
|

Triggering risk factors for ischemic stroke

Abstract: Negative emotions, anger, and sudden changes in body posture in response to a startling event appear to be independent triggers for ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 21 publications
4
78
2
2
Order By: Relevance
“…An analysis of population attributable risk estimated that emotional stress had a role in 3.9% of acute cardiac events (79). The use of case-crossover methods for stroke has been limited, but one study reported an odds ratio as high as 14.0 (95% CI 4.4-89.7) for negative emotion in the two hours before stroke onset (58).…”
Section: Acute Cardiac Eventsmentioning
confidence: 99%
“…An analysis of population attributable risk estimated that emotional stress had a role in 3.9% of acute cardiac events (79). The use of case-crossover methods for stroke has been limited, but one study reported an odds ratio as high as 14.0 (95% CI 4.4-89.7) for negative emotion in the two hours before stroke onset (58).…”
Section: Acute Cardiac Eventsmentioning
confidence: 99%
“…In a study of 200 individuals hospitalized for stroke or transient ischemic attack, approximately 30 reported having extreme episodes of anger, fear, irritability, or nervousness as a result of a startling event within 2 hours before experiencing their stroke. 523 In addition, exposure to a potential trigger may increase stroke risk by as much as 14 times during the 2-hour period immediately after the exposure. Kuroda et al 524 found that women had a higher proportion of poststroke anxiety and depression than men, and although additional findings suggest that women have different coping styles than men after stroke, there remains a paucity of research to clarify sex differences and thus guide appropriate interventions.…”
Section: Inpatient Outpatient and Chronic Care Settingsmentioning
confidence: 99%
“…The literature search finally resulted in 26 studies that met inclusion criteria (Supplemental Figure, available at http://stroke.ahajournals.org), corresponding to 12 potential triggers: alcohol abuse (nϭ10 studies), [21][22][23][24][25][26][27][28][29][30] clinical infection/inflammation (nϭ12), 10,11,29,[31][32][33][34][35][36][37][38][39] stressful life events (nϭ1), 34 psychological distress (nϭ1), 40 birthday (nϭ1), 41 positive or negative emotions (nϭ1), 42 anger (nϭ1), 42 sudden posture change in response to a startling event (nϭ1), 42 heavy physical exertion (nϭ1), 42 heavy eating (nϭ1), 42 and recreational drug abuse (nϭ2). 43,44 Interrater reliability for selection process was perfect (ϭ1.00).…”
Section: Resultsmentioning
confidence: 99%